Does Device Selection Impact Recanalization Rate and Neurological Outcome?: An Analysis of the Save ChildS Study. Issue 4 (April 2020) - Sporns, Peter B.; Straeter, Ronald; Minnerup, Jens; Wiendl, Heinz; Hanning, Uta; Chapot, René; Henkes, Hans; Henkes, Elina; Grams, Astrid; Dorn, Franziska; Nikoubashman, Omid; Wiesmann, Martin; et al.
Abstract : Background and Purpose—: The recent Save ChildS study provides multicenter evidence for the use of mechanical thrombectomy in children with large vessel occlusion arterial ischemic stroke. However, device selection for thrombectomy may influence rates of recanalization, complications, and neurological outcomes, especially in pediatric patients of different ages. We, therefore, performed additional analyses of the Save ChildS data to investigate a possible association of different thrombectomy techniques and devices with angiographic and clinical outcome parameters. Methods—: The Save ChildS cohort study (January 2000–December 2018) analyzed data from 27 European and United States stroke centers and included all pediatric patients (<18 years), diagnosed with arterial ischemic stroke who underwent endovascular recanalization. Patients were grouped into first-line contact aspiration (A Direct Aspiration First Pass Technique [ADAPT]) and non-ADAPT groups as well as different stent retriever size groups. Associations with baseline characteristics, recanalization rates (modified Treatment in Cerebral Infarction), complication rates, and neurological outcome parameters (Pediatric National Institutes of Health Stroke Scale after 24 hours and 7 days; modified Rankin Scale and Pediatric Stroke Outcome Measure at discharge, after 6 and 24 months) were investigated. Results—: Seventy-three patients with a median age of 11.3 years were included. Currently available stent retrievers were used in 59 patients (80.8%), of which 4×20 mm (width×length) was the most frequently chosen size (36 patients =61%). A first-line ADAPT approach was used in 7 patients (9.6%), and 7 patients (9.6%) were treated with first-generation thrombectomy devices. In this study, a first-line ADAPT approach was neither associated with the rate of successful recanalization (ADAPT 85.7% versus 87.5% No ADAPT) nor with the complication rate or the neurological outcome. Moreover, there were no associations of stent retriever sizes with rates of recanalization, complication rates, or outcome parameters. Conclusions—: Our study suggests that neurological outcomes are generally good regardless of any specific device selection and suggests that it is important to offer thrombectomy in eligible children regardless of technique or device selection. Registration—: URL: https://www.drks.de/ ; Unique identifier: DRKS00016528.